Use of four‐layer porcine small intestinal submucosa alone as a scaffold for the treatment of deep corneal defects in dogs and cats: preliminary results. (1st June 2020) - Barachetti, Laura; Zanni, Marco; Stefanello, Damiano; Rampazzo, Antonella
Abstract : Background: To describe the efficacy of four‐layer porcine small intestinal submucosa (Vetrix BioSIS plus+) as single scaffold for the treatment of deep corneal lesions in dogs and cats. Methods: 10 dogs and 3 cats with deep or full thickness corneal defects were treated surgically with BioSIS plus graft. Corneal transparency scores and vision were evaluated. Results: Lesions in dogs were four perforations, three descemetoceles, two limbal melanocytomas and one deep corneal ulcer. In cats, there were one limbal melanocytoma and two perforations. The average length of the follow‐up was 86 days. In all, 12 out of 13 eyes treated were visual at last recheck (92.3 per cent). The scars were mild eight cases (66.7 per cent), but denser in four cases (33.4 per cent). Complication were partial collagenolysis in three cases (25 per cent), which resolved with medical therapy, mild corneal pigmentation in one case (8.4 per cent) and anterior synechia in one case (8.4 per cent). One case experienced severe collagenolysis and was enucleated 21 days postoperatively. Conclusions: Four‐layer porcine SIS graft was successfully used for surgical treatment of deep corneal lesions in selected corneal diseases in a small series of dogs and cats, with good results in terms of mechanic support and corneal transparency.